Perturbed hematopoiesis in mice lacking ATMIN - Anjos-Afonso, Fernando (Blood, 2016)
The ataxia telangiectasia mutated (ATM)-interacting protein ATMIN mediates noncanonical ATM signaling in response to oxidative and replicative stress conditions. Like ATM, ATMIN can function as a tumor suppressor in the hematopoietic system: deletion of Atmin under the control of CD19-Cre results in B-cell lymphomas in aging mice. ATM signaling is essential for lymphopoiesis and hematopoietic stem cell (HSC) function; however, little is known about the role of ATMIN in hematopoiesis. We thus sought to investigate whether the absence of ATMIN would affect primitive hematopoietic cells in an ATM-dependent or -independent manner. Apart from its role in B-cell development, we show that ATMIN has an ATM-independent function in the common myeloid progenitors (CMPs) by deletion of Atmin in the entire hematopoietic system using Vav-Cre. Despite the lack of lymphoma formation, ATMIN-deficient mice developed chronic leukopenia as a result of high levels of apoptosis in B cells and CMPs and induced a compensatory mechanism in which HSCs displayed enhanced cycling. Consequently, ATMIN-deficient HSCs showed impaired regeneration ability with the induction of the DNA oxidative stress response, especially when aged. ATMIN, therefore, has multiple roles in different cell types, and its absence results in perturbed hematopoiesis, especially during stress conditions and aging.